(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Food Crib is a food business that has grown recently. Many people are fond of it, and with the number of customers, issues within the customers and Food crib arise. The researchers come up with this study in regard to customer service. This study aims to come up with ways to sustain and improve customer service to cater to all customers of Food Crib. Based on the results presented, the researchers proposed that the business should maintain or improve the understanding of customers and use their demographic profile as a basis for them. A business should hire an employee who offers fast, accurate, and quality customer service and also has good behavior and understanding skills when it comes to customers' feelings and needs. Have a semi-annual orientation and training for new and old employees. Training and orientation to be able to adapt to every change of trends or desires of customers. Having quality customer service can retain customers. The owner or the establishment should implement the proposed plan and monitor it to see if it is effective in solving the problems encountered by the customers. Always monitor the business, especially the employees, to know if the business is still productive.